Analisis Kesalahan Semantik Pada Skripsi Mahasiswa Jurusan Pendidikan Bahasa Arab UIN Raden Intan Lampung - Zughrofiyatun Najah; Arizka Agustina (Institut Agama Islam Negeri Metro, 2020)
Error analysis is a study that teaches in a practical way about the mistakes committed by the language learner and trying to identify the causes of these errors for how they are solved. Significance is a science that studies the meaning, while the analysis of semantic errors is errors in choosing the appropriate and appropriate word for the meaning of the context of the sentence. A thesis is a scientific thesis written by students with a bachelor's degree and discusses a specific subject or field based on the result of theoretical foundations written by experts or from the results of field research or development research (experimental) This research aims to know semantic errors in scientific theses, a study for students of the Department of Arabic Language Education, College of Education and Teacher Preparation at Radin Intan Islamic State University, Lampung, especially for the analysis of linguistic errors from the semantic and lexical side. This research is qualitative research with the type of library research. The method of collecting the data used is the documentary method in five scientific theses, a study for students of the Department of Arabic Language Education, College of Education and Teacher Preparation at Radin Entan Islamic State University, Lampung for the academic year 2015-2017 in a content analysis method. The researcher found linguistic errors 68 errors semantically, especially in semantic lexical terms. Lexical semantic errors are divided into two parts, namely ambiguity of meaning and accompanying. One of the reasons for semantic errors is the lack of understanding of the previous researcher towards the synthesis of the Arabic word or sentence in the mother tongue or in the use of the terminology of the Arabic word so that the researcher returns the same mistakes again.